2006
DOI: 10.1061/(asce)1090-0241(2006)132:2(237)
|View full text |Cite
|
Sign up to set email alerts
|

Development of Real-Time Safety Control System for Urban Gas Supply Network

Abstract: The seismic safety of city gas supply has been the major research topic of the writers in past decades. To avoid earthquake hazards due to leakage of gas from breakage of buried pipes, a real-time safety control system, SUPREME, has been deployed and put into practical use. SUPREME employs 3,800 new spectrum intensity sensors and remote control devices to achieve quick gas supply shut off. It monitors the earthquake motion at a large number of sites on a real-time basis, interprets the data, and assesses gas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Alaska earthquake monitoring system consists of 11 digital seismic acceleration recorders which monitor ground motion intensity mainly and determine the safety of the pipeline [4]. The seismic monitoring system of the Tokyo gas network is composed of a sensing automatic isolation system and a pipeline earthquake prediction system [5]. Domestic earthquake monitoring and early-warning system has been used less on oil and gas pipeline, so far, only Ji Ning segment of the West-East natural gas pipeline [6] and China Myanmar pipeline during the early stage of the construction were installed monitoring system.…”
Section: Application Status Of Domestic and International Monitoring mentioning
confidence: 99%
“…Alaska earthquake monitoring system consists of 11 digital seismic acceleration recorders which monitor ground motion intensity mainly and determine the safety of the pipeline [4]. The seismic monitoring system of the Tokyo gas network is composed of a sensing automatic isolation system and a pipeline earthquake prediction system [5]. Domestic earthquake monitoring and early-warning system has been used less on oil and gas pipeline, so far, only Ji Ning segment of the West-East natural gas pipeline [6] and China Myanmar pipeline during the early stage of the construction were installed monitoring system.…”
Section: Application Status Of Domestic and International Monitoring mentioning
confidence: 99%
“…It was successfully tested in a 2002 earthquake that generated higher ground motions in Taipei than the Chi Chi did (Shimizu et al 2006). It was successfully tested in a 2002 earthquake that generated higher ground motions in Taipei than the Chi Chi did (Shimizu et al 2006).…”
Section: Early Warning Use For Protection Lifelines and Critical Facimentioning
confidence: 99%
“…They also showed that SI is more strongly correlated with building collapse rate than PGA, which led them to design a sensor, upgraded in 2000 (Shimizu et al, 2000b), to measure the value of SI for use in the immediate post-earthquake control of utility systems with large service areas in Japan. These observations together with a strong correlation between SI and the damage rate of pipelines (Hosokawa et al, 2001;Shimizu et al, 2006) contributed in part to Tokyo Gas Company's decision to deploy 3700 SI sensors in its service area to immediately detect when strong ground motions are expected to have broken buried pipelines (Towhata, 2008;Yamazaki et al, 2001). SI sensors have also been installed in Taipei, Taiwan (Shimizu et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%